Role of Acetone in the Formation of Highly Dispersed Cationic Polystyrene Nanoparticles - Ernawati Lusi; Balgis Ratna; Ogi Takashi; Okuyama Kikuo; Takada Tomonori (Chemical and Process Engineering)
A modified emulsion polymerisation synthesis route for preparing highly dispersed cationic polystyrene (PS) nanoparticles is reported. The combined use of 2,2′-azobis[2-(2-imidazolin- 2-yl)propane] di-hydrochloride (VA-044) as the initiator and acetone/water as the solvent medium afforded successful synthesis of cationic PS particles as small as 31 nm in diameter. A formation mechanism for the preparation of PS nanoparticles was proposed, whereby the occurrence of rapid acetone diffusion caused spontaneous rupture of emulsion droplets into smaller droplets. Additionally, acetone helped to reduce the surface tension and increase the solubility of styrene, thus inhibiting aggregation and coagulation among the particles. In contrast, VA-044 initiator could effectively regulate the stability of the PS nanoparticles including both the surface charge and size. Other reaction parameters i.e. VA-044 concentration and reaction time were examined to establish the optimum polymerisation conditions.